2018
DOI: 10.25134/erjee.v7i1.1530
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning English for Visually Impaired Students: An Ethnographic Case Study

Abstract: In this article we report an ethnographic case study of observing the teaching and learning of English at a school for visually impaired students in Bandar Lampung, Indonesia. Data collection included student and teacher interviews. It also covered class observation and used a social constructivist framework of disability. The study revealed that the students received inadequate modifications of instruction in foreign language learning. However, the students used a variety of resources with the screen reader t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…In addition, the result of this study was also supported by a research from Susanto & Nanda (2018) which found that visually impaired students actually can have unique ways of learning foreign language supported by the assistive technology. In relation to assistive technology, it was also used by the teacher in SLB Negeri 1 Tabanan in the form of JAWS application.…”
Section: Figure 2 Braille With Pen Regletsupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, the result of this study was also supported by a research from Susanto & Nanda (2018) which found that visually impaired students actually can have unique ways of learning foreign language supported by the assistive technology. In relation to assistive technology, it was also used by the teacher in SLB Negeri 1 Tabanan in the form of JAWS application.…”
Section: Figure 2 Braille With Pen Regletsupporting
confidence: 68%
“…The last is use the name of the pupil's or students during class discussions so that the individual knows who is talking. Basically, visually impaired students pose difficulties in learning foreign language since human vision serves as a major stimulus for learning a language Agesa & Arslantaş (in Susanto & Nanda, 2018). Without vision, the students rely on the remaining senses of hearing and motor-kinesthetic feedback in learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of the study, the authors analyzed publications and didactic materials related to the methodology of teaching foreign languages to students with different educational needs. The problem of inclusion of blind and visually impaired people is widely covered in the literature on teaching foreign languages to people with disabilities [5][6][7], which deals with the possibility of using technical means of training [8] and the Internet [9], the peculiarities of the educational process adaptation [10], inclusion strategies and foreign language teaching technology to this category of students [11]. It should be particularly noted that some authors do not refuse to use tactile manuals written in Braille, especially for the study of vocabulary and grammar [12], and offer a methodological model of teaching foreign language for students with special educational needs [13].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the extent of their usefulness or effectiveness is still inconclusive. In their study, Susanto and Nanda (2020) reported that the visually impaired students in Bandar Lampung, Indonesia received inadequate modifications of instruction in English language learning [16]. However, to compensate for the shortcomings, the students took advantage of technology like the screen reader technology or NonVisual Desktop Access (NVDA) and Job Access with Speech (JAWS).…”
Section: Visually Impaired Language Learners and Assistive Technologymentioning
confidence: 99%